2018
DOI: 10.1074/jbc.ra118.004351
|View full text |Cite
|
Sign up to set email alerts
|

Glycoside hydrolase family 18 and 20 enzymes are novel targets of the traditional medicine berberine

Abstract: Berberine is a traditional medicine that has multiple medicinal and agricultural applications. However, little is known about whether berberine can be a bioactive molecule toward carbohydrate-active enzymes, which play numerous vital roles in the life process. In this study, berberine and its analogs were discovered to be competitive inhibitors of glycoside hydrolase family 20 ␤-N-acetyl-D-hexosaminidase (GH20 Hex) and GH18 chitinase from both humans and the insect pest Ostrinia furnacalis. Berberine and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 65 publications
5
47
0
Order By: Relevance
“…In addition, insect chitinases play crucial roles in chitinous tissues and other physiological processes, and thus are new and potent molecular targets. The crystal structure of insect beta-N-acetyl-D-hexosaminidase OfHex1 [ 50 ] and the co-crystal structures with its inhibitors, TMG-chitotriomycin ( Figure 2 D) [ 50 ], PUGNAc [ 51 ], and berberine [ 52 ], were successfully solved. OfHex1 is an enzyme that linked to an “open-close” mechanism at the entrance of the active site; the active pocket size of OfHex1 to TMG-chitotriomycin was Trp 490 , the active pocket size of OfHex1 to PUGNAc was Val 327 , and the active pocket size of OfHex1 to berberine was Trp 322 , Trp 483 , Val 484 , which contributes to its inhibitory activity.…”
Section: Pesticide Targetsmentioning
confidence: 99%
“…In addition, insect chitinases play crucial roles in chitinous tissues and other physiological processes, and thus are new and potent molecular targets. The crystal structure of insect beta-N-acetyl-D-hexosaminidase OfHex1 [ 50 ] and the co-crystal structures with its inhibitors, TMG-chitotriomycin ( Figure 2 D) [ 50 ], PUGNAc [ 51 ], and berberine [ 52 ], were successfully solved. OfHex1 is an enzyme that linked to an “open-close” mechanism at the entrance of the active site; the active pocket size of OfHex1 to TMG-chitotriomycin was Trp 490 , the active pocket size of OfHex1 to PUGNAc was Val 327 , and the active pocket size of OfHex1 to berberine was Trp 322 , Trp 483 , Val 484 , which contributes to its inhibitory activity.…”
Section: Pesticide Targetsmentioning
confidence: 99%
“…Berberine (BBR) is an isoquinoline alkaloid extracted from the rhizomes of Coptis, which displays multiple biochemical functions and anti‐microbial and anti‐inflammatory activities . BBR also exhibits anti‐cancer activities through suppressing cell proliferation and inducing tumour cell apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…Berberine (BBR) is an isoquinoline alkaloid extracted from the rhizomes of Coptis, which displays multiple biochemical functions and anti-microbial and anti-inflammatory activities. 14,15 BBR also exhibits anti-cancer activities through suppressing cell proliferation and inducing tumour cell apoptosis. [16][17][18][19][20][21][22] BBR reportedly directly binds with DNA, radio-sensitizes lung and oesophageal cancer cells and sensitizes ovarian cancer cells to cisplatin and PARP inhibitors.…”
mentioning
confidence: 99%
“…In our previous works, we observed that compounds bearing a large conjugated plane were likely to be potent inhibitors of GH18 chitinase (27,30). In this study, exploiting our previously reported two constructs of OfChtII (OfChtII-C1, residues 1606 -1992; OfChtII-C2, residues 2056 -2438) (8), we screened the compound library of our lab which contains a mass of compounds with a large conjugated plane and obtained four potent inhibitors.…”
mentioning
confidence: 99%
“…Cyclic peptide-based inhibitors, such as argifin, argadin, and their derivatives, mimic the carbohydrate-protein interactions (16 -21). By virtual screening, other inhibitors were also obtained, including methylxanthine derivatives (22)(23)(24), closantel derivatives (25,26), berberine (27), styloguanidine (28) and psammaplins (29). These compounds exhibit inhibitory activities at nanomolar to millimolar levels.…”
mentioning
confidence: 99%